The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.14393/bj-v32n5a2016-32982
|View full text |Cite
|
Sign up to set email alerts
|

Phytomass decomposition and nutrients release from pearl millet, guinea grass and palisade grass

Abstract: ABSTRACT:The objective of this study was to evaluate the production and persistence of biomass of pearl millet (Pennisetum glaucum), guinea grass (Panicum maximum) and palisade grass (Urochloa brizantha), as well as the release rate of macronutrients and Si and changes in cellulose, lignin and the C/N and C/Si ratios of biomass. The experimental design was a randomized block design, with four replications, in a factorial constituted by three cover crops (pearl millet, guinea grass and palisade grass) and six s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
(20 reference statements)
0
7
0
1
Order By: Relevance
“…Urochloa can accumulate between 2 and 16 Mg of dry matter ha −1 in their aerial parts, per year, in crop rotation or intercropping (Macedo, 2009;Bernardes et al, 2010;Costa et al, 2016;São Miguel et al, 2018), with the amount varying according to the species and the system management practices adopted, such as fertilization and cutting timing/frequency.…”
Section: Shoot Biomass and Nutrient Accumulation In Urochloamentioning
confidence: 99%
See 1 more Smart Citation
“…Urochloa can accumulate between 2 and 16 Mg of dry matter ha −1 in their aerial parts, per year, in crop rotation or intercropping (Macedo, 2009;Bernardes et al, 2010;Costa et al, 2016;São Miguel et al, 2018), with the amount varying according to the species and the system management practices adopted, such as fertilization and cutting timing/frequency.…”
Section: Shoot Biomass and Nutrient Accumulation In Urochloamentioning
confidence: 99%
“…According to Costa et al (2014b), it takes 6 months for 90% of all P and K and 60% of all N to be released from the Urochloa residue. To release half of the N, P, K, Ca, and Mg contents of the Urochloa biomass, it takes 52, 20, 16, 61, and 47 days, respectively (Costa et al, 2016). In corn-Urochloa intercrop, up to 89% of U. brizantha and U. ruziziensis residues were already decomposed 3 months after corn harvest (Momesso et al, 2019).…”
Section: Decomposition Of Urochloa Residues and Nutrient Releasementioning
confidence: 99%
“…The maximum N release rate from palisade grass is observed from 0 to 14 days (Fig. 3) after desiccation (Costa et al, 2016a). In black oats, most of the N in plant residues is released up to 34 days after desiccation and is faster than C mineralization (Crusciol et al, 2008).…”
Section: N Cycling In Cropping Systemsmentioning
confidence: 99%
“…In the present study, forages sown in succession to maize showed lower lignin content and C/N ratios due to the younger age of the grasses, a strong indication that this plant material is capable of decomposing more quickly, cycling nutrients and improving soil quality (Costa et al, 2016b). The high production of remaining straw from guinea grass sown in succession to maize enabled greater accumulation of nutrients that can potentially return to the soil.…”
Section: Remaining Straw and Nutrient Contentmentioning
confidence: 46%
“…The remaining straw (mulch) in NTS contributes to soil quality and protection and to nutrient cycling (Crusciol et al, 2015;Costa et al, 2016b;Pariz et al, 2017). For successful implementation of NTS in the tropics, sufficient remaining straw production is key for maintaining favorable conditions for successive planting, as straw is a slow-release source of nutrients for cash crops (Costa et al, 2016b). In contrast to the FDMP results, the amount of remaining straw was highest for guinea grass sown in succession to maize (9.8 Mg ha −1 ).…”
Section: Remaining Straw and Nutrient Contentmentioning
confidence: 99%